EKSPLORASI VISUAL CERITA RAKYAT NUSANTARA DALAM FOTO BERKISAH - Noor Latif CM (Universitas Trisakti, 2019)
AbstractIndonesian Folklore Visual Exploration on Narative Photography. This research begins with the lack of awareness of Photography class students to work on local content in their duties. Students feel foreign and don’t care about the wealth of content they have. In some cases sending students abroad requires a portfolio that has a strong local identity. Our strength as a multicultural nation that is rich in a variety of cultures andtraditions is an attraction worth selling. These problems were not realized by students and teachers, especially photography classes. The results of this study are expected to later be an input to the photography learning material. Besides that, it can also be an inspiration for other subjects in developing local content in their learning material. In this study, taking the case of Nusantara Folklore will be done in a creative projectthrough photography. The project will be attended by several selected photography class children. The method to be carried out in this study uses the Artistic Research on Art approach, where the object of the research is the process of creating photographic works in the project that are carried out communally . Every student works on a topic offolklore that is different from other students. Their photography work in this research project will be exhibited by inviting participants from other countries’ campuses. AbstrakEksplorasi Visual Cerita Rakyat Nusantara dalam Foto Berkisah. Penelitianini berawal dari minimnya kesadaran mahasiswa kelas Fotografi untuk menggarap konten lokal dalam tugas-tugasnya. Mahasiswa merasa asing dan tidak peduli dengan kekayaan konten yang dimiliki. Dalam beberapa kasus pengiriman mahasiswa ke luarnegeri dibutuhkan portfolio yang memiliki identitas kelokalan kuat. Kekuatan kita sebagai bangsa multikultur yang kaya akan ragam budaya dan tradisi menjadi dayatarik layak jual. Permasalahan tersebut kurang disadari oleh mahasiswa dan juga pengajar, terutama kelas fotografi. Hasil dari penelitian ini diharapkan dapat menjadi masukan terhadap materi pembelajaran fotografi selain itu dapat juga menjadi inspirasi matakuliah lain dalam mengembangkan konten lokal dalam materi pembelajarannya.Dalam penelitian ini mengambil kasus Cerita Rakyat Nusantara yang dikerjakan dalam sebuah proyek kreatif melalui fotografi. Proyek tersebut akan diikuti oleh beberapa anak kelas fotografi yang terpilih. Metode yang akan dijalankan dalam penelitian ini menggunakan pendekatan Artistic Research on Art, di mana obyek penelitiannya adalah proses penciptaan karya fotografi dalam proyek tersebut yang dilakukan secara komunal.Setiap mahasiswa mengerjakan topik cerita rakyat yang berbeda dengan mahasiswa lain. Karya fotografi mereka dalam proyek penelitian ini nantinya akan dipamerkan dengan mengajak peserta dari kampus negara lain.